PERANCANGAN IDENTITAS WAJAH EKOWISATA SUBAK SEMBUNG DENGAN MEMADUKAN KEINDAHAN ALAM DAN KONSERVASI BUDAYA - Timang, E.A.; Putra, I.G.A.M.; Chandra, V.; Saputra, T.R. (Buletin Udayana Mengabdi, 2024)
Ecoutourism as a concept of tourism development with an environmental focus, has received significant attention in recent years for its focus on sustainability practices and conservation efforts. Subak Sembung, as one of the ecotourism destinations which located in the Peguyangan Village, North Denpasar, Bali, expected not only offer the beauty of green rice fields but also to integrate that natural beauty with culutal values. The presence of a gateway at Subak Sembung as a face identity plays a crucial role in providing the first impression, attracting visitors, and simultaneously serving as the receiver for visitors to enter the Subak Sembung area. It is essential to plan the design of face identity of Subak Sembung that not only showcases the beauty of the surrounding environment but also reflects the significant cultural values, allowing visitors to experience tourism while gaining a new perspective in appreciating the aspects of natural beauty and their connection to cultural conservation.